Primary versus secondary antiemetic prophylaxis with NK1 receptor antagonists in patients affected by gastrointestinal malignancies and treated with a doublet or triplet combination regimen including oxaliplatin and/or irinotecan plus fluoropyrimidines: A propensity score matched analysis - Parisi, Alessandro; Giampieri, Riccardo; Mammarella, Alex; Felicetti, Cristiano; Salvatore, Lisa; Bensi, Maria; Maratta, Maria Grazia; Strippoli, Antonia; Filippi, Roberto; Satolli, Maria Antonietta; Petrillo, Angelica; Daniele, Bruno; et al. (Frontiers in Oncology, 2022)
Aim The aim of the current study is to investigate the impact of primary compared to secondary chemotherapy-induced nausea and vomiting (CINV) prophylaxis with NK1 receptor antagonists (NK1-RA) in patients affected by gastrointestinal malignancies and treated with oxaliplatin- and/or irinotecan-based doublet or triplet regimens. Study design and methods Clinical data of patients affected by gastrointestinal malignancies, treated with an oxaliplatin and/or irinotecan-based doublet or triplet regimen as neo/adjuvant or advanced-line treatment, and who received NK1-RA as primary (from the first cycle of treatment) or secondary (after the onset of CINV with a previous regimen with 5HT3-RA and dexamethasone) prophylaxis for CINV, were retrospectively collected in an observational study involving 16 Italian centers. A propensity score matching was performed by taking into account the following stratification factors: sex (male vs. female), age (< vs. ≥70 years old), overweight (body mass index, BMI < vs. ≥25), underweight (BMI < vs. ≥19), disease spread (early vs. advanced/metastatic), tumor type (esophagogastric cancer vs. the rest, hepatobiliary tumor vs. the rest, colorectal cancer vs. the rest), type of NK1-RA used as primary/secondary prophylaxis (netupitant-palonosetron vs. fosaprepitant/aprepitant), concomitant use of opioids (yes vs. no), concomitant use of antidepressant/antipsychotic drugs (yes vs. no), Eastern Cooperative Oncology Group (ECOG) performance status at the start of NK1-RA treatment (0 vs. 1–2), and intensity of chemotherapy regimen (doublet vs. triplet). Results Among 409 patients included from January 2015 to January 2022 and eligible for analysis, 284 (69%) and 125 (31%) were treated with NK1-RA as primary and secondary antiemetic prophylaxis, respectively. After matching, primary NK1-RA use was not associated with higher rates of protection from emesis regardless the emesis phase (acute phase, p = 0.34; delayed phase, p = 0.14; overall phase, p = 0.80). On the other hand, a lower rate of relevant nausea (p = 0.02) and need for rescue antiemetic therapy (p = 0.000007) in the overall phase was found in primary NK1-RA users. Furthermore, a higher rate of both complete antiemetic response (p = 0.00001) and complete antiemetic protection (p = 0.00007) in the overall phase was more frequently observed in primary NK1-RA users. Finally, chemotherapy delays (p = 0.000009) and chemotherapy dose reductions (p = 0.0000006) were less frequently observed in primary NK1-RA users. Conclusion In patients affected by gastrointestinal malignancies, a primary CINV prophylaxis with NK1-RA, 5HT3-RA, and dexamethasone might be appropriate, particularly in those situations at higher risk of emesis and in which it is important to avoid dose delays and/or dose reductions, keeping a proper dose intensity of chemotherapy drugs.